Adding value to home compost: Biopesticide properties through Bacillus thuringiensis inoculation. (1st April 2020) - Ballardo, Cindy; Vargas-García, María del Carmen; Sánchez, Antoni; Barrena, Raquel; Artola, Adriana
Graphical abstract: Highlights: Home compost properties were enhanced by Bacillus thuringiensis (Bt) inoculation. Quality home compost with added biopesticide properties was obtained from biowaste. Crystal toxin was present in the compost after Bt progress during home composting. Microbiological analysis revealed highly diverse communities in home compost. Abstract: Home and community composting are considered potential tools for the self-management of organic waste. The production of added value products from biowaste is an encouraging step further to valorise this waste stream. To increase the profits of homemade compost, this paper presents a strategy to produce enriched home compost with biopesticide properties through a simple and low-cost process. Bacillus thuringiensis (Bt) was inoculated in a home composter bin through a solid inoculum previously prepared using the same waste as substrate. The process was monitored and compared with a home composting control process without inoculation. Final composts were analysed and compared in terms of physicochemical and microbiological properties, respiration and germination indices, indicating the suitability of both to be used as organic amendments. Also, a standardized toxicity test proved that Bt-enriched compost can be safely applied to the soil. Microbiological analysis revealed highly diverse communities in both cases, with limited differences at phylum taxonomic level, but dissimilar relative abundances of species within phylum. Bacteroidetes and Proteobacteria were dominant, with the presence of species able to transform organic matter from vegetal origin, but not usually related to compost. Bt-cristal toxin was clearly present in Bt-enriched compost, indicating the coexistence of Bt with the different microbial populations till the end of the composting process. Although Bt has been widely investigated due to its biopesticide properties, the incorporation of this microorganism to home composting level has not been previously reported.